Determination of Carbofuran on Hydrophilic Interaction Liquid Chromatography using TSKgel®Amide-80 as a Stationary Phase - Kurnia, Asep; Lim, Lee Wah; Takeuchi, Toyohide (UI Scholars Hub, 2016)
Hydrophilic interaction liquid chromatography (HILIC) equipped with an environmentally friendly capillary column was employed to investigate the retention behavior of carbofuran; a polar stationary phase was used as well. Several conditions were conducted to investigate the retention behavior of carbofuran, such as a comparison study TSKgel®Amide-80 with another polar column, a comparison study retention behavior of carbofuran on various wavelengths, the water content effect on HILIC mode, the effect of buffer concentration on HILIC mode, and the analytical performance of carbofuran. The results showed that TSKgel®Amide-80 exhibited a better performance than other polar stationary phases in carbofuran determination, and observations at wavelengths of 251 and 254 nm showed higher absorbance for carbofuran than others. In addition, the increase of water content and salt buffer concentration in the mobile phase led to a shorter retention time. The recovery of this method was 101 ± 10.1%, while the limit of detection and the limit of quantification were 0.66 ppm and 2.22 ppm, respectively. Consequently, TSKgel®Amide-80 offers a good perform